Founding the American colonies - Reische, Diana L. (New York : F. Watts, 1989)
Describes the founding, problems, and social and economic survival of the original thirteen American colonies.
Includes index.
Booklist.
5.8
5-8
Keywords: United States -- History -- Colonial period, ca. 1600-1775 -- Juvenile literature; United States -- History -- Colonial period, ca. 1600-1775.; United States -- History -- 1600-1775, Colonial period; United States -- History -- Colonial period, ca. 1600-1775.